(untitled) (Web of Teachers: Inderscience Research, 2026)
The article examines a level-based exercise system for developing reading competence among philology students through ICT tools. The proposed model includes five stages: Focusing, On the Line, Between the Lines, Beyond the Lines, and Reflection. The study argues that this sequence supports students’ gradual movement from literal comprehension to inferential, critical, and reflective reading.